Alternate inks for arbuscular mycorrhizal root staining - Wilkes, Thomas I. (The Microbiology Society, 2023)
Alternate methods for root staining of arbuscular mycorrhizal (AM) fungi have recently gained more attention for the reduction of hazard exposure to the user. Sheaffer® blue ink has been employed for such an identification and quantification, having shown and increased degree of image clarity. However, sourcing Sheaffer® blue ink is becoming problematic, leading to the need to find alternative inks that are readily available. Parker® ink is a well-known brand, providing comparable colour option to Sheaffer®. Two Parker® inks, blue and washable blue, were employed alongside Sheaffer® blue for comparative AM fungal root staining. From quantified AM fungal vesicles and arbuscles, along with the degree of stained image clarity under microscopy, none of the inks utilised for this comparison produce a significantly (P=0.97) different AM fungal quantification or change in image clarity. Therefore, results of the present communication suggest that Parker® blue and washable blue inks are alternative ink stains for the viewing and quantification of AM fungi in host cortical root tissues.
Keywords: Parker ink; root tissue; Arbuscular Mycorrhizal fungi; ink staining; Sheaffer ink